Integration of pedagogical technologies developed for healthy and auditory impaired students - I. N. Lunina; M. V. Pokrovskaya; E. V. Rezchikova (Высшее образование в России, 2022)
The authors state that in a certain sense the learning problems of different groups of students (healthy and auditory impaired) are similar and can be solved by common pedagogical methods. The article presents the ways of integration of pedagogical technologies developedfor healthy and hearing-impaired students. This integration can ensure the system educational effect and enables to raise the graduates’ competence level. In particular the authors suggest using method of mind maps and concept maps.